Atracurium-induced anaphylaxis and angioedema: a case report - Sharma, Jyoti; Verma, Savita; Gupta, M. C. (International Journal of Basic & Clinical Pharmacology, 2017)
Drug-induced anaphylaxis has increased in frequency with the more widespread use of pharmaceutical agents. Neuromuscular blocking agents (NMBAs) are one of the most common causes of anaphylaxis during general anesthesia. However, the incidence of anaphylaxis due to atracurium is very rare (<1/10,000) according to UK Summary of Product Characteristics. NMBAs can induce two types of reactions: one is immune mediated - immunoglobulin E dependent and the second one is associated with non-specific stimulation of mast cells. Systemic manifestations of anaphylaxis can be in the form of hypotension, difficulty in breathing. Rarely, it can be associated with cutaneous manifestations such as urticaria, angioedema, and flushing. If it is not promptly diagnosed and treated, it can be fatal. In the present case, the patient was posted for submandibular gland surgery. She was well-stabilized after general anesthesia and within the seconds of giving injection atracurium; she had difficulty in breathing and marked decrease in blood pressure that was soon followed by periorbital swelling and swelling of lips. The patient was diagnosed with anaphylaxis with angioedema due to atracurium and was promptly managed in operation theater. She was kept under observation for 2 days. Anaphylaxis along with angioedema with atracurium is a very rare event, and hence it is being reported here.